PENGEMBANGAN MEDIA PEMBELAJARAN “ MISUZ “ UNTUK MENINGKATKAN HASIL BELAJAR AL-QUR’AN HADIST MATERI HUKUM BACAAN MIM KELAS V MI/SD - Fitria, Risda Lailul Yulfa; Hidayah, Khamidatun; Mala, Asnal (Universitas Islam Darul 'Ulum Lamongan, 2024)
The purpose of this research is to develop misuz learning media material on the law of reading Mim Al-Qur'an Hadith in class V MI/SD in order to make it easier to understand the material and obtain meaningful learning. This research method uses a literature study or literature study. This research was conducted in six stages, namely 1) The stage of choosing a theme according to the media development information. 2) Information exploration. 3) The stage of determining the direction of research 4) The stage of collecting data sources, data sources are taken based on information relevant to the theme 5) Presentation of data and preparing reports. In the analysis, selection, comparison, merging, and sorting will be carried out so that what is relevant is found. Checking between libraries and paying attention to the supervisor's comments is carried out in order to maintain the immutability of the process of evaluating, preventing and eliminating misinformation. The results of this study indicate that misuz learning media can improve learning outcomes and can be used as a supporting tool in the learning process. It can be concluded that misuz learning media can provide fun learning and is suitable for use as a learning media for class V MI/SD material on the law of reading memes in learning Al-Qur'an Hadith